Zmiany struktury przestrzennej obszaru Zabłocia w Krakowie objętego lokalnym programem rewitalizacji - Świerczewska-Pietras, Katarzyna (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2011)
Cracow’s area of Zabłocie, covered by the local revitalization programme, was formed during  the development of industrial plants in 18 th  and 19 th  century. The local business activities included  the Factory of Nets, Furniture, Ferrum Constructions and Ornament Goods owned by Józef Gorecki,  whose products, even today, embellish the interiors of the Old Theater, the Chamber of Commerce  and Industry, or the Cracow’s Soap Factory owned by Czesław Śmiechowski (currently Miraculum),  which was the largest plant of this type in Krakow. The area of Zabłocie also housed the city’s largest  distillery plant, “Cracow Vodkas”, as well as the Polish Healthy Bread Manufacture “Ziarno”. After the  Second World War the post-industrial Zabłocie changed its production profile from technically simple  to technologically advanced goods. Gorecki’s factory was replaced with “Telpod”, which, following  political transitions of the 1990’s, was declared bankrupt.  During the political transformation as well as at the end of the nineties, Zabłocie became “the  forgotten” area of Kraków. The ongoing deterioration of post-industrial buildings as well as spacial and  infrastructural chaos influenced the deepening processes of the area’s functional structure within the  territory of the city. It was only the municipality, which objective was to bring the district out of crisis  and which based its politics on passing of both local plan of spacial economy and local revitalization  programme, that generated investors’ interest in the area. Currently Zabłocie is undergoing revitalization  works on post-industrial buildings which, thanks to new functions, can be again incorporated into the  area’s spacial structure. With regard to the above, the objective of this essay is to present structural  changes which the district has undergone over the course of recent years and which have significantly  influenced its functional transition from post-industrial to the one oriented on development of small and  medium enterprises sector and housing.